Multiphonic spectromorphology : structuring potential sound multiplicities within the acoustic framework of the saxophone in an experimental practice-based artistic research compositional process - Freire, Sérgio Monteiro (2023)
Orientador: Dr. Felipe de Almeida Ribeiro